2013
DOI: 10.1074/jbc.m113.505727
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Carboxyl-terminal Insert Domain in the Hematopoietic-specific, GTPase-deficient Rho GTPase RhoH Regulates Post-translational Processing

Abstract: Background: RhoH is required for T cell development and non-coding RhoH mutations are found in B-cell lymphoma. Results: The C-terminal insert domain regulates RhoH protein stability via chaperone-mediated autophagy. Conclusion: Although the insert domain is required for lysosomal uptake, it is dispensable for T cell development. Significance: Targeting the insert domain may permit alteration of RhoH protein levels without impairing vital protein functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…We and others have demonstrated that RhoH acts as an adaptor protein associating with the Src-family protein tyrosine kinase Lck, c-Src tyrosine kinase Csk, and Syk-family protein tyrosine kinase Zap70 and Syk [ 6 8 ]. Because RhoH is anchored to the plasma membrane through myristoylation, it is able to recruit Lck, ZAP70, and Syk to the membrane to facilitate membrane proximal signal transduction [ 6 , 7 , 9 ]. Ligation of TCR by MHC/peptide complexes induces phosphorylation of TCR-ζ chain ITAMs by Lck, thereby initiating TCR-dependent signal transduction.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have demonstrated that RhoH acts as an adaptor protein associating with the Src-family protein tyrosine kinase Lck, c-Src tyrosine kinase Csk, and Syk-family protein tyrosine kinase Zap70 and Syk [ 6 8 ]. Because RhoH is anchored to the plasma membrane through myristoylation, it is able to recruit Lck, ZAP70, and Syk to the membrane to facilitate membrane proximal signal transduction [ 6 , 7 , 9 ]. Ligation of TCR by MHC/peptide complexes induces phosphorylation of TCR-ζ chain ITAMs by Lck, thereby initiating TCR-dependent signal transduction.…”
Section: Introductionmentioning
confidence: 99%
“…Another gene, ENSG00000168421, is the tumor suppressor RHOH, a member of the Ras superfamily. Considering that this gene is expressed in hematopoietic cells, it is quite suitable for it to act as a liquid biopsy marker for the differential diagnosis of tumor [ 43 , 44 ]. Although this gene has been confirmed to contribute to tumorigenesis, there are few reports on it.…”
Section: Discussionmentioning
confidence: 99%
“…Rnd1, Rnd2, Rnd3, and RhoH/TTF represent a completely distinct group of proteins within the Rho family (Riou et al 2010;Troeger et al 2013), as they do not share several conserved and essential amino acids, including Gly-12 (Rac1 numbering) in the G1 motif (also called phosphate-binding loop or P-loop) and Gln-61 (Rac1 numbering) in the G3 motif or switch II region. The role of these residues in GTP hydrolysis is well described for Ras oncogene in human cancers (Chaps.…”
Section: Rho Family and The Molecular Switch Mechanismmentioning
confidence: 99%